41 Reduced arterial wave reflection and enhanced LV relaxation contribute to warm-up angina. (9th June 2011) - Lockie, T P E; Guilcher, A; Rolandi, C; Perera, D; De Silva, K; Williams, R; Siebes, M; Chowienczyk, P; Redwood, S; Marber, M
Abstract : Background: The mechanisms of the clinically observed phenomenon of reduced angina on second exertion, or warm-up angina, are poorly understood. This study compared changes in central haemodynamics, peripheral wave reflection and patterns of coronary blood flow during serial exercise that may contribute. Methods and Results: 16 patients (15 male, 61±4.3 yrs) with a positive exercise stress test and exertional angina completed the protocol. During cardiac catheterisation via radial access they performed 2 consecutive exertions (Ex1, Ex2) using a supine cycle ergometer. Throughout exertions, distal coronary pressure (Pd ) and flow velocity ( V ) were recorded in the culprit vessel using a dual sensor coronary guide wire while aortic pressure was recorded using a second wire. Time to 1 mm ST depression was longer in Ex2 (p=0.003) and rate pressure product (RPP) was higher (p=0.025) confirming warm-up. A 33% decline in aortic wave reflection (p<0.0001) in Ex2 (see Abstract 41 figure 1A ) coincided with a reduction in both tension time index and diastolic time index (p<0.0001). However, the latter was offset by reduced microvascular resistance (Pd / V ), p=0.0002, and enhanced left ventricular relaxation during Ex2 as suggested by a larger backward-travelling suction wave (p=0.01) on wave intensity analysis (WIA) of the intra-coronary signals. See Abstract 41 figure 1B . The energy of the forward compression wave and overall coronary blood flow, as measured by the velocity time integral, did not change. Conclusions: In patients with warm-up angina, exercise induces changes in the aortic pressure waveform, microvascular function and LV relaxation. These combine to reduce afterload without compromising myocardial diastolic blood flow thereby likely enabling improved performance on second exercise.